Admission time and outcomes of patients admitted to intensive care unit in a tertiary hospital in Nepal: an observational study - Paudel, Ashmita; Acharya, Subhash Prasad; Shrestha, Gentle Sunder; Shrestha, Pramesh Sunder; Paneru, Hem Raj; Sharma, Sachit (Journal of Nepalese Society of Critical Care Medicine, 2024)
Background and aims: Time of admission to the intensive care unit may have a significant impact on the outcome. However, there is scarcity of published literature regarding admission hours and outcomes from low-income and middle-income countries like Nepal. The aim of this study was to compare the outcome of patients admitted to intensive care units at office hours and off hours. Methods: This observational study was conducted in the intensive care units of Tribhuvan University Teaching Hospital, Kathmandu, Nepal. Data from 1 January 2020 to 31 December 2022, over a period of three years, were curated from the ICU registry. Patients were divided into two groups based on the time of admission to intensive care unit: 1) office hours (from 9:00 am till 4:59 pm that day) and 2) off hours (5:00 pm to 8:59 am next day, including Saturdays and public holidays). Results: Among 3733 patients admitted to ICU, 3242 patients were enrolled for analysis. There were no significant differences in mortality rate as well as average duration of mechanical ventilation between two groups. The average length of stay was however longer by 1 day among patients admitted during off hours compared to office hours. Conclusion: The time of admission in ICU has no significant effect on the outcome of patients. Off hour ICU admission is not associated with poor patient outcomes compared to office hours.